2020
DOI: 10.18488/journal.64.2020.81.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Internal Nutrient Load Dynamics from the Sediment in Lake Ziway

Abstract: Article HistoryKeywords Lake Ziway Internal nutrient load Phosphorus flux Sediment depth profile. Lake Ziway is shallow freshwater located in Northern part of Ethiopian Rift Valley. Expansions of the flower industry, widespread fisheries, intensive agricultural activities, fast population growth lead to deterioration of both water and sediment qualities and depletion of aquatic biota. The main objective of this study is to evaluate the internal nutrient load dynamics from the sediment. Nutrients in sediment sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Studies conducted in different catchment areas showed that water resources are vulnerable to nutrient loads from agricultural fields, urban drainage systems and industrial centres. Tibebe et al (2018) and Tibebe et al (2020) conducted external nutrient loading and trophic status of Lake Ziway, in the Ethiopian Rift Valley. In their study, water samples from the Ziway River were collected over two years (2014 and 2015) and chemical analysis was determined for nutrient concentrations according to the American Public Health Association (APHA).…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…Studies conducted in different catchment areas showed that water resources are vulnerable to nutrient loads from agricultural fields, urban drainage systems and industrial centres. Tibebe et al (2018) and Tibebe et al (2020) conducted external nutrient loading and trophic status of Lake Ziway, in the Ethiopian Rift Valley. In their study, water samples from the Ziway River were collected over two years (2014 and 2015) and chemical analysis was determined for nutrient concentrations according to the American Public Health Association (APHA).…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%